Methotrexate disposition, anti-folate activity and efficacy in the collagen-induced arthritis mouse model - Singh, Rakesh K. (Eur J Pharmacol, 2019)
Methotrexate (MTX) efficacy in autoimmune arthritis is variable and unpredictable resulting in the need for the identification of biomarkers to guide drug therapy. This study utilizes the collagen-induced arthritis mouse model to investigate erythrocyte MTX disposition and anti-folate activity as biochemical markers of efficacy in autoimmune arthritis. Following induction of arthritis, DBA/1J mice were treated with once-weekly subcutaneous MTX at varying doses over a period of 40 days. At the completion of the study tissue samples were analyzed for MTX and folate content and assessed for their relationship with MTX efficacy. MTX treatment resulted in a reduction in disease activity that was variable and dose-dependent. Erythrocyte accumulation of MTX and its polyglutamate metabolites were dose proportionate, however, polyglutamate metabolites represented a mean±S.E.M. of 8.9±0.4% of total erythrocyte MTX, which is markedly lower than previously observed in humans and failed to display any significant association with MTX efficacy. MTX treatment resulted in reductions in erythrocyte 5-methyl-tetrahydrofolate (5mTHF) levels that were similar to those previously observed in human studies. Disease induction was associated with a decrease in liver 5mTHF and increased formyl-tetrahydrofolate (fTHF) that was normalized in MTX treated mice. MTX efficacy was associated with reductions in erythrocyte 5mTHF (P=0.04) and increases in liver 5mTHF (P=0.0001). Together, these findings demonstrate a relationship between alterations in tissue folate levels and MTX efficacy, and supports erythrocyte levels of 5mTHF as a marker of MTX efficacy in autoimmune arthritis.